Meningkatkan Kualitas Pembelajaran IPS dengan Model Kooperatif Course Review Hooray di SD Negeri 10 Kepahiang - Supriogi, Supriogi (UNIB Press, 2020)
At SD Negeri 10 Kepahiang, there are still teachers who haven’t implemented innovative learning, still became the center of the class, and students were too passive. The learning outcomes became mimimum. Because action is needed to improve the quality of learning, and Course Review Hooray might be the answer. The purpose of this study was to improve teaching skills, increase student activity, and improve learning competencies in Social Science. The study was divided into three cycles, each cycle divided into planning, implementing, observing and reflecting. The results in Cycle I, the student learning outcomes obtained a 44% completeness. In Cycle II, the learning outcomes increased with a completeness of 67%. In Cycle III, the average value of student learning outcomes obtained a completeness of 93%. Thus, conclusion can be drawn, by using the Course Review Hooray Cooperative Learning Model the quality of Social Science has increased impressively.